A Comparison of Specific Nonconjugated Conductive Polymers for Application as Protective Shields against Nuclear Radiation including Radioactive Iodine - Govula, Kirthana; Thakur, Mrinal (European Journal of Applied Sciences, 2026)
Nonconjugated conductive polymers have been shown to be uniquely suited to protective applications against nuclear radiation including radioactive iodine. In this report, we discuss comparative studies of four important nonconjugated conductive polymers for capturing iodine from air and water for the nuclear shielding applications. These four polymers include: cis-polyisoprene, trans-polyisoprene, poly(β-pinene) and styrene butadiene rubber (SBR). The studies discussed here included measurements of iodine uptakes (doping) over time, consequent increases in electrical conductivities and recorded color changes. In terms of capturing iodine or radioiodine from air and water, cis-polyisoprene has the highest efficiency (fastest), followed by SBR, trans-polyisoprene and poly(β-pinene). These differences arise from variations in molecular structure, chain packing, morphology, and availability of doping sites which impact diffusion dynamics in the formation of charge-transfer complexes. Stopping radioiodine (vapor phase) escaping from nuclear reactors and extracting radioiodine from contaminated water are both significant objectives which can be uniquely achieved by these nonconjugated conductive polymers. Nuclear reactors should be covered by such a polymer to protect against radioiodine emission / leakage to the outside.